Dangerous passengers: multidrug-resistant bacteria on hands and mobile phones - Martina, Pablo F. (2019)
Introduction. It is recognized that mobile phones may play arole in microorganism transmission and that hand hygiene, isconsidered the most important action for preventing infectionsand the spread of pathogens. The objective of this study wasto determine presence and circulation bacteria on hands andmobile phones capable of causing infections in people and alsodetermine if disinfection with gel-alcohol is useful to reduce thebacterial colonization.Methods. The bacterial evaluation included 596 hands of participantsand 256 mobile phones. Isolated colonies were identifiedby biochemical test and confirmed by gene 16S rRNAsequencing. Antimicrobial susceptibility was performed usingthe automated instrument Vitek®2-Compact and disk-diffusionmethod.Results. In total, 92.9% of mobile phones and 98.3% of participantsin study demonstrated evidence of bacterial contaminationwith different types of bacteria. Surprisingly, we observedthat 18.6% plaques inoculated with disinfected fingers showedbacterial growth. In general, Gram negative isolates showedresistance to a higher number of antibiotics tested than Grampositive isolates.Conclusions. Our results could help to raise awareness in oursociety about the importance of hand hygiene, as well as frequentlyused devices, reducing bacterial contamination andlimiting the possibility of transmission of resistant multi-drugbacteria.